(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article presents data on the study of biological and morphological characteristics of 15 varieties of tree paeonia during introduction in the conditions of the forest-steppe zone of the Bashkir Cis-Ural. Quantitative and qualitative features were analyzed. Their research was carried out in accordance with the «Test methodology for distinctness, uniformity and stability». The phenotypic variability of quantitative parameters was studied. A positive high correlation was noted between the flower diameter and the length of the longest tepal. The revealed patterns are of interest for building a model of paeony varieties and using them in plant breeding.